Crystal structure of 4-(2,2-difluoroethyl)-2,4-dimethyl-6-(trifluoromethyl)isoquinoline-1,3(2H,4H)-dione, C14H12F5NO2 - Liu Jianlian; Du Chaojun; Hao Hong (Zeitschrift für Kristallographie - New Crystal Structures)
C14H12F5NO2, monoclinic, P21/c (no. 14), a = 11.8292(10) Å, b = 11.0987(8) Å, c = 11.6480(10) Å, β = 115.282(11)°, V = 1382.8(2) Å3, Z = 4, Rgt(F) = 0.0913, wRref(F2) = 0.1609, T = 293(2) K.